Multicolor flow cytometry on pericardial effusion for a prompt diagnosis and treatment of hematological malignancies with heart involvement - Cappannoli, Luigi; Imazio, Massimo; Hohaus, Stefan; Saponara, Gianluigi; D’Amario, Domenico; Bellesi, Silvia; Maiolo, Elena; Viscovo, Marcello; Fatone, Federica; Alma, Eleonora; D’Alò, Francesco; Crea, Filippo; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background Malignancies represent 15–50% of total causes of pericardial effusions (PE). Routine analyses recommended to be performed on pericardial fluid include general chemistry, cytology, polymerase chain reaction, and microbiological cultures. Multicolor flow cytometry (FC) is a laboratory test that already proved to be useful in the detection of lymphoproliferative and metastatic malignancies in pleural and peritoneal effusions, but current guidelines do not mention its use on PE to reach a diagnosis. Methods Our institutional protocol foresees to routinely perform a multicolor FC analysis on pericardial fluid samples obtained by pericardiocentesis, in addition to other guidelines-recommended analyses. A sample of 15–30 ml is analyzed using a lyse and wash staining method using combination panels of antibodies, allowing to detect specific cellular subpopulations, analyzing tens to hundreds of thousands of cells in few seconds. The present manuscript aims to report our single-center experience with this diagnostic tool in patients presenting with PE requiring pericardiocentesis. Results Routine use of multicolor FC on pericardial fluid samples in our institution allowed to reach a definite diagnosis of cardiac lymphomas in two patients presenting with otherwise unexplained severe PE. This resulted in immediate start of combined immunotherapy, with patients’ clinical improvement. At 6 months follow-up both patients are alive and presented a complete disease regression. Conclusion Preliminary evidence from routine use of multicolor FC on PE support that this is a promising tool to reach a rapid diagnosis of hematological malignancies with heart involvement, leading to a prompt initiation of targeted therapies.